THE INFLUENCE OF READING INTEREST AND LIBRARY ACCESS TOWARDS STUDENTS’ READING ACHIEVEMENT - Sri Endah Kusmartini (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2013)
The research was designed to examine the influence of reading interest of English StudyProgram students, Sriwijaya State Polytechnic and library access as perceived by the studentsthemselves towards their reading achievement. The number of the sample was 60 which were takenrandomly. A measure of reading interest was used to measure reading interest of the students and ameasure of library access was used to measure their perception about library access. The archive aboutstudents’ reading scores from English Study Program, Sriwijaya State Polytechnic was used to see theirreading achievement. Pearson Product Moment and Multiple Linear Regression were used to test thehypotheses. The results proved that there was significant correlation between reading interest ofEnglish Study Program students, Sriwijaya State Polytechnic and their reading achievement; there wassignificant correlation between library access as perceived by English Study Program students,Sriwijaya State Polytechnic and their reading achievement; reading interest of English Study Programstudents, Sriwijaya State Polytechnic added to library access as perceived by the students themselvesinfluenced their reading achievement significantly.